Report of The Five Year Plan Committee - Planning Commission (Planning Commission, 1960)
In the course of the discussion of the Budget for 1961-62 at the thirty-ninth meeting of the Executive Council of the Institute held on the 17th December, I960 a suggestion was made that a memorandum might be prepared describing the activities which the Budget was providing for and that it was also desirable to have information of the activities that were likely to be pursued over a period of the next five years.
The Indian Institute of Public Administration
Planning Commission Government of India